Disorder-driven sintering-free garnet-type solid electrolytes - Giyun Kwon; Hyeokjo Gwon; Youngjoon Bae; Changhoon Jung; Dong-Su Ko; Min Gyu Kim; Kyungho Yoon; Gabin Yoon; Sewon Kim; In-Sun Jung; Sangjun Lee; Taehee Kim; et al. (Nature Communications)
Abstract Oxide ceramic electrolytes for realization of high-energy lithium metal batteries typically require high-temperature processes to achieve the desired phase formation and inter-particle sintering. However, such high-temperature processing can lead to compositional changes or mechanical deformation, compromising material reliability. Here, we introduce a disorder-driven, sintering-free approach to synthesize garnet-type solid electrolyte via the creation of an amorphous matrix followed by a single-step mild heat-treatment. The softened mechanical property (yield pressure, P y  = 359.8 MPa) of disordered base materials enables the facile formation of a dense amorphous matrix and the preserving of inter-particle connectivity during crystallization. The formation of the cubic-phase garnet is triggered at a lowered temperature of 350 °C, achieving a Li+ ionic conductivity of 1.8 × 10–4 S/cm at 25 °C through a single-step mild heat treatment at 500 °C. The disorder-driven garnet solid electrolyte exhibits electrochemical performance comparable to conventional garnet solid electrolyte sintered at >1100 °C. These findings will promote the fabrication of uniform, thin, and wide solid electrolyte membranes, which is a significant hurdle in the commercialization of oxide-based lithium metal batteries, and demonstrate the untapped capabilities of garnet-type oxide solid electrolytes.